1988
DOI: 10.1152/ajpheart.1988.255.6.h1443
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and sympathoadrenal responses to mental stress: influence of beta-blockade

Abstract: Cardiovascular, sympathoadrenal, and subjective responses to mental stress induced by a color-word conflict test (CWT) were studied in 30 healthy males before and after intravenous administration of either placebo, beta 1-blockade by metoprolol (0.15 mg/kg), or nonselective beta-blockade by propranolol (0.15 mg/kg). CWT responses were reproducible. Mean arterial pressure increased by 20%. A mainly heart rate-dependent 65% increase in cardiac output (thermodilution) was associated with 25% decreases of both sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 0 publications
8
93
1
1
Order By: Relevance
“…Increase in PR, SBP one hour prior to exam occurs possibly as a result of sympathetic activation. This is consistent with the findings of Freychuss et al & Malathi et al who contributed it to increased epinephrine levels 1,3 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Increase in PR, SBP one hour prior to exam occurs possibly as a result of sympathetic activation. This is consistent with the findings of Freychuss et al & Malathi et al who contributed it to increased epinephrine levels 1,3 .…”
Section: Discussionsupporting
confidence: 93%
“…Other researchers also reported a similar trend of increasing pulse rate, blood pressure, and galvanic skin resistance during examination stress. 1,12 Our study also observed that 29(60.4 %) male and 47 (78.3%) female students were having increase in pulse rate and systolic blood pressure one hour before the examination compared to pulse rate(PR) and systolic blood pressure(SBP) ten days before and ten days after the examination. Bazmi Inam 13 has noted prevalence of increase anxiety in females to be 89.7% and males 60% in 1st year medical students of Saudi Arabia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…To generalize, mental tasks elicit primarily cardiac output (mostly heart rate)-mediated elevations in arterial pressure (Hejl, 1957) as observed in most subjects in this study. Studies of responses to mental tasks during f8-blockade (Nyberg, Graham & Stokes, 1977;Freyschuss, Hjemdahl, Juhlin-Dannfelt & Linde, 1988) suggest that if one mechanism (e.g. heart rate) for elevating arterial pressure during the task is constrained or eliminated, a different mechanism will compensate so that a given increase in arterial pressure is generated.…”
Section: Discussionmentioning
confidence: 99%
“…Rise in BP due to stress leads to increased epinephrine secretion and this rise in BP is important sympathoadrenal response to physiological stressful experience caused by pre-menstrual stress. [16] Most evidence suggest that there is decrease in serotonin and beta-endorphins level during pre-menstrual phase and this might be associated with changes in mood and behavioral symptoms. [1,17,18] Thus during different phases of menstrual cycle neurohormonal changes, stress, and sympathetic activity are interrelated to each other.…”
Section: Discussionmentioning
confidence: 99%